Islamic Radicalism: Between Accusation and Reality - Muntasir Muntasir (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2019)
This paper discusses about islamic radicalism is accusation or reality. The essence is that similar acts of radicalism are also carried out by people of other religions in the world. This signifies that radicalism is actually not an issue of Islam, but it is a matter of the human race, whatever religion is adopted. Apart from various views that unilaterally claim that radicalism is synonymous with Islam, the reality can be said that radicalism is also carried out by followers of other religions. The manifestation of acts of violence committed by the human ummah which do not exclude any legitimate religion that they adhere to is driven by despair towards various highly unwanted phenomena. Terror acts are the last alternative after various other choices have a dead end.